Batik Stamp Training for PKK Mothers to Build Entrepreneurial Spirit - Utaminingsih, Alifiulahtin; Permatasari, Qurnia Indah; Maskan, Mohammad (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service aimed to cultivate entrepreneurial spirit among productive-age PKK mothers in RW 10 Sekarpuro Village, Pakis District, Malang Regency. The primary goal was to enhance their income generation capabilities and productively utilize their free time through creative economic activities. Method: A structured batik stamp training program was implemented, utilizing accessible materials and simple stamp-making techniques that can be easily replicated by participants, addressing human resource development needs. Practical Applications: The training focused on developing practical skills in batik stamp production with creative and innovative designs that have economic value, enabling participants to produce marketable handicrafts. Conclusion: The training successfully equipped participants with skills to become reliable entrepreneurs in stamped batik, demonstrating potential for sustainable income generation and community economic development through creative industry engagement.